An Interdisciplinary Approach for Improved Functional and Esthetic Results in an Adult Patient - Case Report - Loredana Golovcencu; G. Zegan; D. Anistoroaei (Romanian Society of Oral Rehabilitation, 2011)
In contemporary dental care an increased number of adult patients are seeking orthodontic treatment. In such adult patients, a combined orthodontic and other specialized therapy often offers the best options for achieving a predictable outcome to solve complex clinical problems. This case report demonstrates a combined therapy with orthodontic and implant- prosthodontic treatment in a 26 years old female patient with class II malocclusion, crowding in the maxillary anterior region, cuspid cross bite and loss of first upper premolar and lower first molar. The patient was treated with a straight-wire orthodontic appliance. Active orthodontic treatment was completed in 25 months and an implant supported prosthesis was placed with a single crown in the region of upper first right premolar.We demonstrate that combined orthodontic-implant-prosthodontic treatment can achieve an improved aesthetics, occlusion and masticatory function.